Model Pendidikan Non Formal Menuju Pembangunan Bidang Pendidikan yang Partisipatif (Studi di â€œKampung Inggrisâ€ Desa Tulungrejo Kecamatan Pare Kabupaten Kediri) - Diarwati, Lerin (Jurnal Administrasi Publik, 2015)
Abstract: Non Formal Education Model Toward Participative Education Development (Study at â€œKampung Inggrisâ€ Tulungrejo Village Pare Municipality, Kediri Regency). Non formal education model in the form of course institutions, but successfully met the demand of communities for life skill. Communities then developed this institution into the famous icon, called as â€œKampung Inggrisâ€. Non formal education model in â€œKampung Inggrisâ€ consisted of (1) inputs, such as instrumental input of course institutions, raw input of educated participant, and environmental input of investors and immediate communities; (2) process, when three inputs were interacting to each other; (3) outputs, that concerned with quality and quantity of educated participants; and (4) impacts, as related to the effect that had been experienced by course institutions, educated participants, investors and immediate communities. It was suggested that; (1) publication must be extended through media; (2) the quality of tutors should be improved; (3) the support from local government might be needed by being responsive to the development of â€œKampung Inggrisâ€; and (4) synchronization should be made between course institutions, investors, immediate communities and local government in maintaining the existence of non formal education in â€œKampung Inggrisâ€. Keywords: non formal education model, Kampung Inggris, participative. Abstrak:Model Pendidikan Non Formal Menuju Pembangunan Bidang Pendidikan Yang Partisipatif (Studi di â€œKampung Inggrisâ€ Desa Tulungrejo Kecamatan Pare Kabupaten Kediri). Model pendidikan non formal dalam bentuk lembaga kursus mampu memenuhi kecakapan hidup masyarakat.Tekad masyarakat dalam mengembangkan kawasan tersebut menjadikan ikon â€œKampung Inggrisâ€ semakin terkenal. Model pendidikan non formal di â€œKampung Inggrisâ€ terdiri dari (1) input yaitu, masukan instrumen berupa lembaga kursus, masukan mentah berupa peserta didik, dan masukan lingkungan berupa investor dan masyarakat sekitar; (2) process yaitu, adanya ketiga masukan yang saling berinteraksi; (3) output yaitu, kualitas dan kuantitas peserta didik; dan (4) impact yaitu, pengaruh yang dirasakan oleh lembaga kursus, peserta didik, investor dan masyarakat sekitar. Saran dari penelitian ini, adalah; (1) publikasi diperluas melalui media; (2) kualitas tutor ditingkatkan; (3) perlu adanya dukungan peran pemerintah setempat yang lebih responsif terhadap perkembangan di â€œKampung Inggrisâ€; dan (4) upaya sinkronisasi antara lembaga kursus, investor, masyarakat sekitar dan pemerintah setempat dalam menjaga eksistensi pendidikan non formal di â€œKampung Inggrisâ€. Â  Kata kunci: model pendidikan non-formal, Kampung Inggris, partisipatifÂ